Case Report: Barely Able to Speak, Can’t Stop Echoing: Echolalic Dynamic Aphasia in Progressive Supranuclear Palsy - Berthier, Marcelo L.; Hoet, Florencia; Beltrán-Corbellini, Álvaro; Santana-Moreno, Daniel; Edelkraut, Lisa; Dávila, Guadalupe (Frontiers in Aging Neuroscience, 2021)
The diagnostic criteria for progressive supranuclear palsy (PSP) incorporate two speech-language disturbances (SLD), nonfluent/agrammatic primary progressive aphasia and progressive apraxia of speech, but overlook the inclusion of dynamic aphasia (DA). Thus, there is a need to reappraise the broad spectrum of SLD in PSP to include other presenting phenotypes. Here we report findings from the study of two elderly patients with PSP presenting with DA and irrepressible echolalia. Both patients had markedly impoverished verbal production, but speech production in other tasks (repetition and naming) and auditory comprehension were preserved or mildly impaired. Experimental tests of DA revealed impaired word and sentence generation in response to verbal and non-verbal stimuli. Additional language and cognitive testing revealed different types of echolalia (mitigated, automatic, and echoing approval) as well as impaired inhibitory control and social cognition (mentalizing). Brain magnetic resonance imaging showed atrophy of the brainstem and superior medial frontal cortex in both patients. Our findings suggest that neurodegeneration in the brainstem, superior medial frontal lobe (pre-supplementary motor area), and caudate nucleus is not only responsible for DA, but it also triggers verbal echoing by disinhibiting perisylvian language cortex activity.